Measurement of Financial Leverage in the Presence of Unfunded Pension Obligations. - Dhaliwal, Dan S. (The Accounting Review, 1986)
Abstract ABSTRACT: This study examines empirically whether unfunded vested pension obligations that are not recorded in corporate balance sheets are viewed as a form of debt by the capital market participants when assessing firm risk. This is accomplished by using a model developed by Hamada [1972] which relates the systematic risk of a firm to its financial risk and business risk. The explanatory power of the model is improved when unfunded vested pension liabilities are included in the measurement of financial leverage. Furthermore, the effect of unfunded vested pension liabilities on market-perceived risk of the firm is not significantly (statistically) different from that of debt and other liabilities.